2016
DOI: 10.1108/jhtt-10-2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Aggregating social media data with temporal and environmental context for recommendation in a mobile tour guide system

Abstract: Purpose-Increasingly manufacturers of smartphone devices are utilising a diverse range of sensors. This innovation has enabled developers to accurately determine a user's current context. One area that has been significantly enhanced by the increased use of context in mobile applications is tourism. Traditionally tour guide applications rely heavily on location and essentially ignore other types of context. This has led to problems of inappropriate suggestions and tourists experiencing information overload. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Some studies indicate the importance of using technologies in a strategic manner especially in terms of social media and online presence. (Reino et al, 2016), the vast number of applications that near field communication technologies have for the tourism industry (Egger, 2013), the use of intelligent context-aware recommender system that takes into account temporal and social context in tour guide applications (Meehan et al, 2016) or the strategic use of Customer Relationship Management systems in tourism as a whole (Vogt, 2011, Mohammed et al, 2017.…”
Section: Strategic Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate the importance of using technologies in a strategic manner especially in terms of social media and online presence. (Reino et al, 2016), the vast number of applications that near field communication technologies have for the tourism industry (Egger, 2013), the use of intelligent context-aware recommender system that takes into account temporal and social context in tour guide applications (Meehan et al, 2016) or the strategic use of Customer Relationship Management systems in tourism as a whole (Vogt, 2011, Mohammed et al, 2017.…”
Section: Strategic Ismentioning
confidence: 99%
“…Content requirement, functional requirement, comfort, experience and resistance are significant user requirement for developing the wearable AR museum application(tom Dieck et al, 2016). Given the heavy reliance of location-based recommendation in tour guide application,Meehan et al (2016)'s study found that environmental, temporal and social these three contextual conditions at a significantly higher level of influence in mobile recommender systems.In terms of research into ICT from a perspective of user support, studies investigated the supportive role of interactive mobile technologies in hotel guests' facilitation of transactions. The adoption of these technologies can mediate the experiences of guests in hotel service settings, with importance placed on cognitive absorption, playfulness, and security (WendyZhu and Morosan, 2014).…”
mentioning
confidence: 99%
“…O papel das tecnologias, especialmente as de comunicação, evidencia a cada dia a relação entre a cocriação de valor e a intenção de recomendação boca-a-boca (WoM). O uso das tecnologias parece aumentar a cocriação de valor no turismo de pelo menos duas maneiras: primeiro, elas permitem a personalização de produtos turísticos e suas experiências (Hsu, King, & Buhalis, 2016;Meehan, Lunney, Curran, & McCaughey, 2016;Sarmah, Rahman, & Kamboj, 2017); segundo, seu uso amplia o alcance das interações sociais, permitindo que turistas e outras partes interessadas compartilhem suas opiniões (positivas ou negativas) em diferentes plataformas (Novak & Schwabe, 2009;Cabiddu, Lui, & Piccoli, 2013). Isto significa dizer que a cocriação de valor e o compartilhamento dessas experiências são estimuladas.…”
Section: Engajamento Cocriação De Valor E Intenção De Recomendação Bunclassified
“…This can often be problematic in a fast-paced industry, which can also be prone to delays and last-minute changes. According to Meehan et al, (2016), social media gives people the opportunity to provide feedback and share thoughts regarding their travel experiences. Customer experience is everything in the airline industry.…”
Section: Figure 1 Social Media User Around the Worldmentioning
confidence: 99%